VIBRATIONAL SPECTROSCOPY OF PHASE TRANSITIONS IN LEONITE-TYPE MINERALS - Hertweck B.; Libowitzky E. (My University, 2002)
Infrared (IR) and Raman spectra of leonite-type minerals, K2Me(SO4)(2).4H(2)O (Me = Mg, Mn, Fe), confirm a succession of structural phase transitions between 277 and 120 K. Because the orientation and dynamic behaviour of the sulphate tetrahedra undergo the most conspicuous changes during these transitions, transmission IR and Raman spectra were recorded for the SO4 bending and stretching modes from 660 to 1230 cm(-1) (IR) and 350 to 1250 cm(-1) (Raman), in a temperature range between 80 K and room temperature. At low temperature the leonite-type minerals show an order-disorder phase transition due to the freezing of the dynamic sulphate disorder. These phase transitions are characterised by non-linear shifts of the peak positions as a function of temperature in IR and Raman spectra. Evaluation of the peak widths of the sulphate modes in the IR and Raman spectra by autocorrelation analysis show non-linear decreases of the width parameters, confirming a tricritical ordering process according to the Landau order parameter. With decreasing temperature the crystal structures of the Mg- and Mn-endmembers switch to another ordered phase. These structural changes are accompanied by the sudden appearance of additional sulphate stretching and bending modes and by discontinuities of the peak shifts in IR and Raman spectra, indicating a first order phase transition.